ANALYSIS OF STUDENTS' CONCEPT UNDERSTANDING CAPABILITY USING PROSPEROUS EQUIPMENT IN 30 STATE JUNIOR HIGH SCHOOLS, TEBO DISTRICT - Wiji Lestari, Tri; Muslimahayati, Muslimahayati; Bestari, Hendra (Journal of Curriculum and Pedagogic Studies (JCPS), 2023)
The purpose of this study was to analyze the ability to understand students' mathematical concepts in determining the surface area of ​​a flat side shape of cubes and blocks with the help of teaching aids. This research method uses qualitative methods with a descriptive approach. This study describes students' ability to understand mathematical concepts with the help of visual aids. The subjects of this study were 6 class VIII A students at SMP Negeri 30 Tebo District. The instruments used were written tests and interview guidelines. Based on the results of the study, it was shown that the ability to understand students' mathematical concepts in the matter of surface area of ​​blocks and cubes with the help of visual aids in class VIII A of SMP Negeri 30 Tebo Regency was generally in the medium category with the average result showing that students obtained a score of 75.5. Subjects S1 and S2 can only achieve one indicator of the three indicators of students' ability to understand mathematical concepts given. Subjects S9 and S11 could only achieve two indicators of the three indicators of students' ability to understand mathematical concepts given. While subjects S31 and S32 were able to achieve all three indicators of ability to understand mathematical concepts from the three indicators of students' ability to understand mathematical concepts given that they were able to restate concepts, classify objects according to certain characteristics and apply concepts algorithmically.